Key Drivers of Customer Satisfaction in Nepalese Mobile Banking Services - Aryal, Narayan Prasad; Singh, Govind Kumar (Journal of Development Review, 2025)
This study aims to explore the factors influencing customer satisfaction with mobile banking services of Nepalese commercial banks. The quantitative research method included descriptive, relational, and causal designs. A response of descriptive, correlational analysis and regression was conducted with IBM SPSS. There were 384 responses from commercial banks. Frequency, percentage, mean, median, mode, standard deviation, variance, correlation, and regression were used to evaluate structured questionnaire data. The result showed that service quality and perceived usefulness have positive and significant impact on mobile banking services. In contrast, customer support and assistance has insignificant and negative relationship with mobile banking services. Regression analysis identified service quality as having the highest impact on customer satisfaction, followed by perceived usefulness, while customer support and assistance has a negligible effect. The study emphasises the importance of service quality and perceived usefulness in enhancing customer satisfaction with mobile banking services.